A Qualitative Inquiry into The Adherence of Adults Type 2 Diabetes Mellitus with Dietary Programs - Kusnanto Kusnanto; Elfa Lailatul Izza; Tri Johan Agus Yuswanto; Hidayat Arifin (Universitas Airlangga, 2019)
Introduction: Diabetes mellitus (DM) is a chronic disease with the characteristic of treatment complexity. The toughest challenge for DM patients is dietary adherence. On the other hand, the socio-culture is one of the factors that influences dietary adherence. The aim of this study was to examine the dietary adherence of adults with type 2 Diabetes mellitus (T2DM), particularly to dietary programs.Methods: This study used a qualitative case study design with a positivist approach. The total participants consisted of 14 T2DM patients obtained through snowball sampling. The research phenomenon was the adherence of adults with type 2 Diabetes mellitus to dietary programs. The data collection was conducted through in-depth interviews with question guidelines analyzed using qualitative thematic analysis.Results: This study obtained five themes regarding the dietary adherence of T2DM patients such as activity, motivation, intention, behavior, and the benefits of dietary adherence. The focus points were activity, motivation, and the intention to comply with the dietary recommendations, including reducing the fatty and fried foods consumed. The patients who felt the benefits of complying with the dietary program found following the dietary adherence to be easier.Conclusions: Activity, motivation, intention, behavior and the benefits of the dietary adherence program all make it easier for the patient to comply with their diet. This result suggests that health workers should provide education to the patients on the importance, benefits and the way to comply with the T2DM dietary program.